Risk Factor , Protective Factors, And Intervention Strategies For Academic Burnout Among University Students : A Systematic Literature Review - Meyllen Joltuwu; Arif Rachman; Agus Sutaraman; Arfiyanti (Journal of Innovation Research and Knowledge, 2026)
Academic burnout is a widespread psychoeducational condition in secondary and tertiary education, characterized by emotional exhaustion, cynicism toward learning activities, and a decreased sense of academic efficacy. The prevalence of academic burnout is reported to reach more than 70 percent in some student populations in high load study programs, with significant impacts on mental health, academic achievement, and study continuity. The fragmentation of previous studies, which usually focus on specific populations or interventions, has resulted in the lack of a comprehensive mapping of the determinants and strategies for addressing academic burnout across educational contexts. This review aims to synthesize the latest empirical evidence on the risk aspects, protective factors, and effectiveness of academic burnout interventions through a systematic literature review strategy referring to the PRISMA 2020 guidelines. A literature search was conducted in Scopus, Web of Science, Google Scholar and PubMed databases with publications spanning the past ten years, yielding 20 articles that met the inclusion criteria. Thematic synthesis findings indicate that academic burnout is influenced by the interaction between individual factors such as emotion regulation and resilience, structural factors such as academic load and institutional support, and sociodemographic factors. Mindfulness based interventions have been shown to be effective in reducing emotional exhaustion and academic cynicism. These findings underscore the importance of a multidimensional approach in designing academic well-being policies in educational institutions